Synergistic Effects of L-Carnitine and Arabic Gum on Oxidative Stress and Adipokines in Hyperlipidaemic Rats - Mohammed Al-Ardawi; Ennas Al-khozaae (Babcock University Medical Journal, 2025)
Objective: The present study was conducted to investigate the combined effects of Arabic gum and L-carnitine on oxidative stress markers and serum concentrations of leptin and adiponectin in male albino rats subjected to diet-induced hyperlipidaemia